Financial Feasibility Analysis Of Voerseri Business (Packaging Bird Feed From Kersen/Singapore Cherry) - Ridho Affandi; Muhammad Reza Siregar; Dini Indira Sari; Nadila Savira; Syuhada Wulantiya; Akbar Habib (JASc (Journal of Agribusiness Sciences), 2019)
Voerseri is a packaged bird feed made from singapore cherry. Voerseri is one of the developing businesses in the city of Medan. The financial feasibility analysis of the voerseri business is carried out to help the Voerseri Business see the feasibility of the development business that will be carried out. Some of the things studied in the financial feasibility analysis include variable costs, fixed costs, and business feasibility criteria which include Break Even Point (BEP), R / C ratio and B / C ratio. The result of the calculation of the financial viability of the Voerseri Business is that it will reach BEP by selling 79 units of products or Rp. 1,330,258 every month. The R / C value obtained is equal to 1.44, which means that this business is feasible to be cultivated while the B / C value obtained is equal to 0.44, which means that this business does not provide benefits to businessmen.